2013
DOI: 10.1128/aem.03784-12
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Hydroxy Fatty Acids Produced during Sourdough Fermentation: Microbial and Enzymatic Pathways, and Antifungal Activity in Bread

Abstract: Lactobacilli convert linoleic acid to hydroxy fatty acids; however, this conversion has not been demonstrated in food fermentations and it remains unknown whether hydroxy fatty acids produced by lactobacilli have antifungal activity. This study aimed to determine whether lactobacilli convert linoleic acid to metabolites with antifungal activity and to assess whether this conversion can be employed to delay fungal growth on bread. Aqueous and organic extracts from seven strains of lactobacilli grown in modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 37 publications
5
126
0
1
Order By: Relevance
“…A variety of systems to prevent food spoilage have been investigated mainly because of the consumers demand for natural products instead of chemicals such as food preservatives (Gray and Bemiller, 2003). The current study confirmed the antifungal properties of LAB bioingredients indicating a synergistic role of organic acids (mainly phenyllactic) and proteinaceous compounds in their efficacy, as also previously suggested (Lavermicocca et al, 2000;Gerez et al, 2010;Black et al, 2013;Ryu et al, 2014;Ryan et al, 2011). In addition the influence of the carbon source or acid precursors on the organic acid production by a selected Lactobacillus brevis strain was demonstrated.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A variety of systems to prevent food spoilage have been investigated mainly because of the consumers demand for natural products instead of chemicals such as food preservatives (Gray and Bemiller, 2003). The current study confirmed the antifungal properties of LAB bioingredients indicating a synergistic role of organic acids (mainly phenyllactic) and proteinaceous compounds in their efficacy, as also previously suggested (Lavermicocca et al, 2000;Gerez et al, 2010;Black et al, 2013;Ryu et al, 2014;Ryan et al, 2011). In addition the influence of the carbon source or acid precursors on the organic acid production by a selected Lactobacillus brevis strain was demonstrated.…”
Section: Discussionsupporting
confidence: 87%
“…In the latter study a L. brevis strain was selected to produce bioingredients efficient in improve yeast-leavened bread shelf life and its textural properties without affecting the leavening performance of S. cerevisiae (Valerio et al, 2014). The genus Lactobacillus was frequently involved in the antifungal activity of LAB as recently reported by some authors (Stiles, 1996;Gerez et al, 2009Gerez et al, , 2013Ryan et al, 2011;Ryu et al, 2014;Black et al, 2013) and the majority of identified antifungal substances are organic acids, hydroxy fatty acids, hydrogen peroxide, reuterin and proteinaceous compounds. Lactic and acetic acids are the main products of the fermentation of carbohydrates by LAB that generally diffuse through the membrane of the target organisms (Axelsson, 1990) in their hydrophobic undissociated form and then reduce cytoplasmatic pH and stop their metabolic activities.…”
Section: Introductionmentioning
confidence: 95%
“…Antifungal lactic acid bacteria (LAB) have been studied in a range of foods and feed like sourdough (Black et al, 2013;Lavermicocca et al, 2000), dairy products (Schwenninger and Meile, 2004) fermented vegetables (Yang and Chang, 2010), and silage (Ström et al, 2002). While most of the efforts have been directed towards finding new potent strains, there is an increasing interest in understanding the antifungal mechanism including the identification and quantification of bioactive compounds produced by these strains.…”
Section: Introductionmentioning
confidence: 99%
“…acting as antibiotic or anti-inflammatory [19]. A range of (R)-α-hydroxy fatty acids (C 14 -C 18 ) has shown antimicrobial activities against plant pathogenic organism such as Vibrio tyrogenuses [39], while (R)-α-and β-hydroxy fatty acids (C 10 -C 12 , and C 14 ) have shown antifungal activity against molds such as Aspergillus fumigatus, Penicillium commune and many more [17,[39][40][41]. Some β-hydroxy fatty acids (e.g.…”
Section: Physiological Roles and Chemical Applications Of Hydroxy Fatmentioning
confidence: 99%